My opinion or yours? An investigation on the effects of individual traits and group influences on the attitude-behaviour relationship. - Lum, Meiyin. (2008)
Past research has established that attitudes are reliable predictors of future behavior. This study explores how the relationship between consumer attitudes and behaviour (purchase intention) would be affected by interpersonal influence in a group.